The Effect of Low Insurance Literacy and Service Levels through Technological Innovation on Digital Business Performance at PT. Asuransi Tri Pakarta - Teguh Pambudi; Derriawan Derriawan; Agustinus Miranda W (Interdisciplinary Social Studies, 2026)
The study was conducted with the aim of analyzing the effect of low insurance literacy and service level on digital business performance with technological innovation as a mediating variable. The research method employed was a descriptive quantitative approach using Stata. A sample of 210 respondents from customers of PT. Asuransi Tri Pakarta was utilized. The findings indicated that: 1) there is a direct effect of insurance literacy on digital business performance, 2) there is a direct effect of service levels on digital business performance, 3) a direct effect of technological innovation on digital business performance was found, 4) there is a direct effect of insurance literacy on technological innovation, 5) there is a direct effect of service levels on technological innovation,  6) an indirect effect of insurance literacy on digital business performance through technological innovation was identified, and 7) an indirect effect of service levels on digital business performance through technological innovation was also found. Thus, it can be concluded that both direct and indirect effects contribute to the success of this research.